Formability of 2195-T4 Al–Li alloy sheet by electromagnetic forming - Haiping Yu; Yanye Jin; Xiao Cheng (Journal of Materials Research and Technology, 2024)
This study explored the efficacy of electromagnetic forming in addressing the limited formability of aluminum–Lithium (AlLi) alloy at room temperature, focusing on the AA2195-T4 sheet. Comparative analyses were conducted to assess the formability. The results indicated that the limit strains obtained through electromagnetic forming were at least 50%, 10%, and 50% higher compared with those obtained through rigid punch forming under the uniaxial tension, plane strain, and biaxial tension. Upon utilizing forming limit diagrams, the failure processes during electromagnetic flanging were predicted. Notably, electromagnetic flanging enabled the creation of hole-flanging structures with a 60% increase in the flanging limit strain around the circumference, surpassing the capabilities of rigid punch flanging. Moreover, the maximum time window for electromagnetic flanging was extended to 168 h. Analysis of the flanging strain path indicated that cracks were prone to occur near round corners during electromagnetic flanging, contrasting with rigid punch flanging where cracks tended to form near the edges of straight walls. This study offered valuable insights for aerospace component formation utilizing Al–Li alloys at room temperature.